Monetary policy and its impact on inflation in Iraq after 2003 - Fadel Krayah Kazaar Al-Shaibani (Journal of Madenat Alelem University College, 2018)
Monetary policy is an effective economic policy in the face of inflation ,as a fundamental and important part of the components of the general economic policy of any country. Thispolicy plays its role by influencing the volume of money supply in a manner that is  appropriate to prevailing economic conditions ,in order to absorb the cash surplus. After 2003 witnessed the Iraqi economy, in both monetary and  real stage of the new changes took place ,the most important of which was the independence of the central Bank of Iraqi ,according to law 56 of 2004 in the formulation of monetary policy , and the identification of appropriate tools to implement this policy, in addition to the development of new  tools ,that fit the orientations of the objectives of monetary policy in Iraq, the most important of which is the stability of prices, and the appreciation of the dinar, through the exchange rate and interest rates. The research was divided in to three sections. The first section included the nature of monetary policy before 2003. The second section dealt with the application of the modern tools of monetary policy after 2003, and the obtaining of the central Bank of Iraq independence. The third section dealt with the effectiveness and efficiency of monetary policy tools in achieving economic stability ,and reducing the inflation ,in addition to the conclusions and recommendations ,where the study confirmed that the use of the central Bank of modern instruments and tools helped him to reach the main goal of controlling inflation ,where the rate of inflation fell from 33.5% in 2003 to 1.9% in 2013 ,and this led to stability in exchange rates, and a stability in the general price level, Therefore, the Iraqi market for securities should be activated and activated through the central Bank.